Near-Field Analysis of Bright and Dark Modes on Plasmonic Metasurfaces Showing Extraordinary Suppressed Transmission - Dobmann, Sabine; Kriesch, Arian; Ploss, Daniel; Peschel, Ulf (Advanced Optical Materials, 2014)
Plasmonic metasurfaces are investigated that consist of a sub-wavelength line pattern in an ultrathin ( 10 nm) silver film, designed for extraordinary suppressed transmission (EOST) in the visible spectral range. Measurements with a near-field scanning optical microscope (NSOM) demonstrate that farfield irradiation resonantly excites antenna-like (bright) modes that are localized on the metal ridges. The re-radiation of these modes into the far-field interferes destructively with the transmitted wave, thus suppressing transmission almost completely. In contrast, a second type of mode, bound (dark) surface plasmon polaritons (SPPs) launched from an NSOM tip, propagates well across the metasurface, preferentially perpendicular to the grating lines.
EAM Import::2019-03-12